(untitled) (Journal of Hama University, 2021)
Coccidiosis is an important enteric parasitic disease of poultry associated with significant economic losses to poultry farmers worldwide due to high morbidity and mortality ratios and low feed conversion, E. tenella is one of the most economically important diseases in broiler chickens. In this study a Post-mortem examination to 300 samples of caecal of broiler chickens performed to determine the intensity of pathological changes resulting from effect of Eimeria Tenella. The main pathological changes in the caecal that was dilation and filled by bloody feces and tissues in addition to Schizonts seen by microcope. Histopathology of caecal of affected birds revealsed a submucosa and lamina propria crowded with large clusters of schizonts. often,large areas of the mucosa are sloughed off, and lesion extended through the muscular layers and the serosal membrane. Scores of infection were divided into four degrees according to the severity of the infection It was noted that the highest incidence of infection was score (3) 35%, followed by score (4) 28.4%, followed by (2) 21.6%, and finally score (1) 15% which was the lowest according to severity of changes and observations.